Obstacles and Difficulties in Implementing the Independent Learning Curriculum in High Schools - Mesta Limbong, Mesta; Asnah MN Limbong (Universitas Pendidikan Ganesha, 2023)
In the curriculum, the teacher has the task of compiling lesson plans, materials, models, methods, assessing, and evaluating. But the fact is that out of 50 students, there are 32 people with a mean value of 28.30. Another fact is that 40% is incomplete. There must be a gap between theory, hope, and reality. The aim is to find out the results of the synthesis, analysis, and evaluation of the implementation of the independent learning curriculum. Mixed method research method. High school subjects and their objects, 90 students and 30 teachers. Data collection techniques with surveys and interviews. Instruments were distributed to respondents with Google from. The next data is the interview. Survey analysis technique with SPSS 26 and formed a bar chart for each indicator. The results of the interviews were analyzed by collecting data, reducing, coding, and drawing conclusions. The data from the survey results are aligned with the results of the interviews and the sliced data becomes the conclusion. The results showed that 39.17% of teachers prepared lesson plans, 31.68% of teachers could teach, 44.12% could assess, only 39.17% of students had changes in behavior and 49.18% were able to assess and evaluate. In conclusion, it is hoped that there will be training in compiling material and assessing and evaluating the learning process on an ongoing basis. This research contributes to providing information on the location of obstacles and difficulties in implementing the independent learning curriculum and this research becomes a reference for teachers, schools, and the government in conducting training.